2008
DOI: 10.3325/cmj.2008.4.536
|View full text |Cite
|
Sign up to set email alerts
|

Psychometric Properties of Croatian and Slovenian Short Form of Oral Health Impact Profile Questionnaires

Abstract: Psychometric properties of OHIP-CRO14 and OHIP-SVN14 render these instruments suitable for the assessment of Oral Health Related Quality of Life in Croatia and Slovenia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
52
1
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(61 citation statements)
references
References 23 publications
7
52
1
1
Order By: Relevance
“…All the inter-item correlations were positive, and none was high enough for any item to be redundant, while the item-total correlations coefficients were above the recommended threshold (0.20) for including an item in a scale, which was also confirmed by research done among Iranians [22]. The validity construction was mostly supported by the subjective criteria as in other studies [13,17,18,21,[23][24][25][26][27]. Our results only confirm previous assumptions according to which dental problems may not only be a source of pain, but may also cause emotional and physical disorders.…”
Section: Discussionsupporting
confidence: 78%
See 2 more Smart Citations
“…All the inter-item correlations were positive, and none was high enough for any item to be redundant, while the item-total correlations coefficients were above the recommended threshold (0.20) for including an item in a scale, which was also confirmed by research done among Iranians [22]. The validity construction was mostly supported by the subjective criteria as in other studies [13,17,18,21,[23][24][25][26][27]. Our results only confirm previous assumptions according to which dental problems may not only be a source of pain, but may also cause emotional and physical disorders.…”
Section: Discussionsupporting
confidence: 78%
“…The results of our study were slightly better than those reported by Ostberg et al, whose results showed that internal consistency measured with Cronbach's alpha was 0.86 for 7 subscales and 0.88 for 14 separate items; similar results were published by Slade who reported high reliability (0.88) [19]. A slightly lower result, but still on a level considered as good or excellent internal consistency, was obtained by Ren [13,[20][21][22][23]. Substantial internal consistency of the instrument in our study was also supported by findings regarding inter-item and item-total correlations.…”
Section: Discussioncontrasting
confidence: 61%
See 1 more Smart Citation
“…The reduced version of this instrument, the OHIP-14, was developed by Slade in 1997, and validated for use in an elderly population in Australia 5 , and in an adult population in England 6 and Scotland 7 . Furthermore, it was translated and trans-culturally adapted in ten languages 8,9,10,11,12,13,14,15,16,17 , including Portuguese 12 . Its validation however, was tested specially on elderly individuals and urban populations, and its use has not been validated for rural populations speaking Latin languages.…”
Section: Introductionmentioning
confidence: 99%
“…Destaca-se a utilização da variável referente à presença ou número de dentes naturais presente em 10 estudos (Gil-Montoya et al, 2013;Hsu et al, 2014;Inukai et al, 2010;Locker & Gibson, 2005;Montero et al, 2008;Motallebnejad et al, 2011;Perea et al, 2013;Pistorius et al, 2013;Wright, 2009;Thomson et al, 2006;); a presença de dentes deteriorados (cariados), perdidos ou obturados e doenças periodontais em 4 estudos (Montero et al, 2008;Montero et al, 2009;Motallebnejad et al, 2011;Thomson et al, 2006); a má oclusão avaliada em 4 estudos (Hsu et al, 2014;Rusanen et al, 2012;Sardenberg et al, 2011;Silvola et al,2012); a utilização de próteses dentárias em 3 estudos (Montero et al, 2008;Perea et al, 2013;Pistorius et al, 2013;Wright et al, 2009); a xerostomia em 2 estudos (Perea et al, 2013;Thomson et al, 2006); a dor facial em 2 estudos Zheng et al, 2011); as disfunções temporomandibulares em 3 estudos (Miettinen et al, 2012;Pereira et al, 2009;Rusanen et al, 2012) e a dor de dentes em apenas 1 estudo (Rener-Sitar et al, 2008).…”
Section: Resultsunclassified